Jute retting water A potential source of essential plant nutrients - Majumdar, Bijan; Sarkar, Sitangshu; Kar, Gouranga (Indian Farming, 2021)
The biochemical process of jute retting involves biodegradation of very high amount of plant biomass (50-60 tonnes/ha) by the enzymatic action of retting microbes present in the retting water resulting in the extraction of jute fibre. During this process of jute retting, the BOD and COD contents in the post-retting water increased many folds because of higher microbial growth, depleted oxygen level and higher suspended organic matter content in post-retting water, although the BOD and COD values were within the safe limit of environmental pollution. The pH of the post-retting water decreased while electrical conductivity increased respectively because of secretion of organic acids from the decomposition of jute and addition of salts like Ca, Mg, iron etc. released from jute plants during retting. Post retting water samples were very rich in primary, secondary and important micronutrients like Fe, Mn, Zn and Cu released from the jute plants during retting. Post-retting water quality parameters to be used for irrigation purposes were found to be within the permissible limits (pH 6.22-7.08, EC 0.509-0.85 ds/m, total N 5.35-26.25 mg/l, P 1.20-4.04 mg/ l, K 10.80-30.50 mg/l, Zn- 0.051-0.6 ppm, Cu-0.11-0.49 ppm, Mn 0.019- 0.22 ppm and Fe 0.30-0.45 ppm).